MERAIH KECERDASAN FINANSIAL BERDIMENSI SPIRITUAL DENGAN WAKAF - Jannah, Diyah Ayu Zahrotul; Haris, Ahmad (ZISWAF, 2017)
In the human world created by bringing the elements of intelligence, be it intelligence quotient or spiritual intelligence. This article aims to reveal the financial intelligence of spiritual dimension with the teachings of waqf. Data collection methods used are with documentation of some literature. The results of the study indicate that the economic downturn has resulted in the inability of education to make a person worse in religious knowledge. Low levels of religious understanding can also lead to more vulnerability to misguided teachings and easily provoked by radical ideas. With waqf, the results obtained from waqf funds can be used for operational costs and educational infrastructure facilities so that people can achieve intelligence and spiritual intelligence so it is not easily provoked by radical ideology and misleading teachings.